Economic valuation of ecosystem services from small-scale agricultural management interventions in Burkina Faso: a discrete choice experiment approach - Houessionon, Prosper; Fonta, William M.; Bossa, A.Y.; Sanfo, S.; Thiombiano, N.; Zahonogo, P.; Yameogo, T.B.; Balana, Bedru (MDPI, 2017)
The main purpose of this paper is to estimate farmers’ preferences and their willingness to pay (WTP) for ecosystem services derived from four agricultural water management (AWM) and resource recovery and reuse (RRR) intervention options in Burkina Faso, using a choice experiment (CE). These include; small water infrastructure, drip irrigation, recovery of organic matter from waste, and treated wastewater. The design decisions relating to attribute selection, the level of attributes, alternatives and choice tasks were guided by literature, field visits, focus group discussions, expert input and an iterative process of the STATA software to generate an orthogonal main-effects CE design. The data used was generated from a random sample of 300 farm households in the Dano and Ouagadougou municipalities in Burkina Faso. Results from conditional logit, latent class logit and mixt logit models show that farmers have positive and significant preferences for drip irrigation, treated wastewater, and organic matter. However, they are WTP on average more for drip irrigation and organic matter for agricultural sustainability. In line with economic theory, the cost of an intervention reduces demand for a given intervention. These findings can provide policy makers with evidence for agricultural policy design to build farmers’ resilience in the Sahel.